Efficient collection and automatic annotation of real-world object images by taking advantage of post-diminished multiple visual markers. (17th December 2019) - Kiyokawa, Takuya; Tomochika, Keita; Takamatsu, Jun; Ogasawara, Tsukasa
ABSTRACT: To collect a human-annotated dataset for training deep convolutional neural networks is a very time-consuming and laborious process. To reduce this burden, we previously proposed an automated annotation by placing one visual marker above the detection target object in the training phase. However, in this approach, occasionally the marker hides the object surface. To avoid this issue, we propose placing a pedestal with multiple markers at the bottom of the object. If we use multiple markers, the object can be annotated even when the object hides some of the markers. Besides that, the simple modification of placing the markers on the bottom allows the use of simple background masking to avoid the neural network learning the remaining markers in the training image as a feature of the object. Background masking can completely remove the markers during the training process. Experiments showed the proposed vision system using our automatic object annotation outperformed the vision system using manual annotation in terms of object detection, orientation estimation, and 2D position estimation while reducing the time required for dataset collection from 16.1 hours to 7.30 hours. GRAPHICAL ABSTRACT: